The Effect of Adding Spent Bleaching Earth on Clay Stabilization to CBR Value - Efan Tifani; Lizar; Noerdin Basir (Himpunan Ahli Teknik Tanah Indonesia, 2025)
SBE (Spent Bleaching Earth) from the process of refining palm oil is recently categorized as non-B3 (hazardous and toxic materials) material by the new Government Regulation of the Republic of Indonesia Number 22 Year 2021 (PP 22/2021) . Not only SBE is abundant, it also has waterproof properties and good cohesion, potentially applicable as subgrade for road when mixed with clay. This paper look into the utilization of SBE to stabilize clay, which usually has a Californian Bearing Ratio (CBR) of 2%, improving its CBR to the minimum required value for subgrade of 6%.The clay specimen used has a fine content of 93.05%, with liquid limit of 45.51% and plasticity index of 17.56%. Based on the AASHTO classification, the clay is categorized as clayey soil (A-7-6). The maximum dry density (MDD) obtained for the clay specimen (100% clay) from the standard proctor test is 1.424 gr/cm3 at an optimum moisture content (OMC) of 18.77%. For a 75% to 25% mixture of clay specimen and SBE, the MDD reduces to 1.318 gr/cm3 and OMC increases to 21.19%. At 50% to 50% mixture of clay specimen and SBE, the MDD further drops to 1.278 gr/cm3 and OMC also further increases to 24.35%. The obtained Laboratory CBR value for 100% clay, 75%-25% clay-SBE mixture and 50%-50% clay-SBE mixture are 4.81%, 3.45% and 2.70%, respectively. From the test results, it can be concluded that addition of SBE does not improve the CBR value.